The Environment of Regulatory T Cell Biology: Cytokines, Metabolites, and the Microbiome - Hoeppli, Romy E.; Wu, Dan; Cook, Laura; Levings, Megan K. (Frontiers in Immunology, 2015)
Regulatory T cells (Tregs) are suppressive T cells that have an essential role in maintaining the balance between immune activation and tolerance. Their development, either in the thymus, periphery, or experimentally in vitro, and stability and function all depend on the right mix of environmental stimuli. This review focuses on the effects of cytokines, metabolites and the microbiome on both human and mouse Treg biology. The role of cytokines secreted by innate and adaptive immune cells in directing Treg development and shaping their function is well established. New and emerging data suggest that metabolites, such as retinoic acid, and microbial products, such as short chain fatty acids, also have a critical role in guiding the functional specialization of Tregs. Overall, the complex interaction between distinct environmental stimuli results in unique, and in some cases tissue-specific, tolerogenic environments. Understanding the conditions that favour Treg induction, accumulation and function is critical to defining the pathophysiology of many immune mediated diseases and to developing new therapeutic interventions.